Microwave imaging of concealed objects beneath clothing by creating synthetic aperture due to natural motion of the subject - Zhuravlev, A.; Razevig, V.; Tataraidze, A.; Chizh, M.; Ivashov, S. (PIERS : 2017 Progress in Electromagnetics Research Symposium-Spring : proceedings : 22-25 May 2017, St. Petersburg, Russia, 2017)
The modern microwave personnel screening systems use either mechanical scanning by a linear array to form synthetic aperture, or electronic switching of the antennas distributed over a surface in a form of a screen or portal. The microwave part of a screening system with mechanical scanning is simpler than the system with electronic switching due to the lesser number of channels. All the modern microwave screening systems have a bulky form factor, which is either a portal or a screen. This paper describes a new architecture of the microwave screening system in which the natural motion of a subject in the vicinity of a linear antenna array is used to form synthetic aperture. Such an architecture allows building a system in the smallest possible form-factor and with the minimal number of antennas with the capability to screen people on the move. In this paper, the experimental data are obtained by the setup consisting of a vector network analyzer and mechanical linear actuators used to move the antennas in the sampling positions. An RGB-D video sensor captures the depth map of the scene, which is later used to coherently process radar data. A mannequin serves as the target and is moved by an additional linear drive to run the imitation experiments following the stop motion technique. The signal processing algorithm is outlined and accompanied by the radar images of concealed objects.